2013
DOI: 10.1074/jbc.m113.506550
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for Scanning and Catalysis on Single-stranded DNA, Illustrated with Activation-induced Deoxycytidine Deaminase

Abstract: Background:A random walk mathematical model is proposed to analyze enzyme scanning and catalysis on ssDNA. Results: The model depicts AID scanning ssDNA in short in random movements, catalyzing C deaminations with minute efficiencies. Conclusion: Clonal mutational data determine scanning dynamics and C deamination efficiencies for AID. Significance: Random walk mathematics can be used to analyze molecular mechanisms generating mutational diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Considering all states of the catalytic pocket regardless of dC accessibility, our modeling and docking results lead us to estimate that 1.3% of all AID-DNA interactions have the potential to result in cytidine deamination. These calculations derived solely from our in silico observations are in good agreement with a recent study that calculated deamination-conducive ssDNA binding events by AID in solution, derived from enzyme kinetic assays (Mak et al, 2013). This study suggested that 0.7%-8.0% of AID-DNA interactions result in dC deamination.…”
Section: The Role Of Dna Binding In Deamination Catalysissupporting
confidence: 90%
“…Considering all states of the catalytic pocket regardless of dC accessibility, our modeling and docking results lead us to estimate that 1.3% of all AID-DNA interactions have the potential to result in cytidine deamination. These calculations derived solely from our in silico observations are in good agreement with a recent study that calculated deamination-conducive ssDNA binding events by AID in solution, derived from enzyme kinetic assays (Mak et al, 2013). This study suggested that 0.7%-8.0% of AID-DNA interactions result in dC deamination.…”
Section: The Role Of Dna Binding In Deamination Catalysissupporting
confidence: 90%
“…It is unlikely that they are physical entry sites for the binding of AID because biochemical studies have shown that AID can bind equally well to single-stranded DNA that does and does not have Cs (67,68). However, AID is a very inefficient enzyme deaminating only one of every 30 dCs it encounters in hotspot motifs (57), so it is possible that the AGCTs in IGHV3-23*01 are often the first site to be deaminated. This is consistent with their being the most frequent site of mutation, but they might sometimes also act as an activation site to extend AID mutation to other sites in some V regions.…”
Section: Discussionmentioning
confidence: 99%
“…These studies confirmed that purified AID had a preference for the AGCT, even on single-stranded DNA. However, it is difficult to extrapolate the in vitro findings to the in vivo events because in the biochemical system, AID both is limiting and is processive through a slide and jump mechanism (56,57). The Ramos cells provide a good cellular model for the initial mutational events that occur in vivo because AID is constantly expressed and the relative susceptibility of the different AID hotspots to mutation is similar to that seen in mice (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A3A activity is also enhanced by cooperative dimerization [265]. Further, the related family member Activation Induced cytidine Deaminase (AID) that deaminates within specific regions of immunoglobulin genes to promote somatic hypermutation and class switching has been characterized as being a catalytically inefficient enzyme [188,266,267]. The low efficiency of catalysis is despite AID's high processivity and ability to remain bound to ssDNA for an average of 5 min [268].…”
Section: Modulation Of Catalytic Activity In the Aid/apobec Familymentioning
confidence: 99%